Enzymatic synthesis of geranyl acetate in packed bed reactor in supercritical carbon dioxide under various pressure-temperature conditions and reactor configurations. (August 2018) - Bourkaib, Mohamed Chafik; Randriamalala, Harifeno; Dettori, Lena; Humeau, Catherine; Delaunay, Stephane; Chevalot, Isabelle; Guiavarc'h, Yann
Graphical abstract: Highlights: Geranyl acetate was enzymatically synthetized in supercritical CO2 using lipase. We used a packed-bed reactor and investigated the impact of residence times (Rt). Based on a DoE a 75% conversion was observed at 65 °C and 150 bar at 8 s Rt. A 98% conversion was observed at 48 s Rt with a high productivity level. Several stability tests revealed a good stability of the lipase. Abstract: As an alternative to the chemical synthesis of geranyl acetate, the aim of the present study is to better understand its enzymatic synthesis in a 1 mL packed bed reactor (PBR) using supercritical CO2 as a green solvent and immobilized lipase B from Candida antarctica as a catalyst. Using a full factorial design in the range 150–300 bar and 45–65 °C, the conversion of geraniol to geranyl acetate versus pressure and temperature could be accurately modeled. The best conversion rate (73.8 ± 0.9%) was observed at 65 °C and 150 bar. Lipase was highly stable at 55 °C–200 bar. In these conditions and due to water accumulation along the PBR, the use of a five-fold longer PBR only led to 73.0 ± 0.1% conversion. The same % conversion could be achieved using 2.5 less enzyme in a two-parallel 1 mL PBR configuration. The positive impact of an increased residence time (Rt) in the PBR was investigated. Conversions of 83% and 98% were achieved with 36 and 27 s Rt at 55 °C–200 bar and 65 °C–150 bar, respectively. These results show that an efficient, green, enzymatic and continuous production of high-purity and solvent-free geranyl acetate is possible with supercritical CO2 .